A support theorem for the Hitchin fibration: the case of SL_n. (26th April 2017) - de Cataldo, Mark Andrea
Abstract : We prove that the direct image complex for theD -twistedSL_n Hitchin fibration is determined by its restriction to the elliptic locus, where the spectral curves are integral. The analogous result forGL_n is due to Chaudouard and Laumon. Along the way, we prove that the Tate module of the relative Prym group scheme is polarizable, and we also prove[STIX]x1D6FF -regularity results for some auxiliary weak abelian fibrations.